A systematic review of supervisory relationships in general practitioner training. Issue 9 (10th May 2019) - Jackson, Dawn; Davison, Ian; Adams, Rachel; Edordu, Adaeze; Picton, Aled
Abstract : Objectives: The educational alliance is argued to be at the heart of supervision in medical education. This review aims to map the research field and develop a conceptualisation of the nature of such educational alliances within postgraduate supervision for general practitioners. Methods: An integrative review of the international literature on supervision from 2011 to 2018 was undertaken, and papers assessed for relevance and quality. Data analysis incorporated framework analysis techniques. Bordin's working alliance‐based model of supervision was used as a springboard for synthesis, as well as allowing for the emergence of new ideas, theories and concepts from the literature. Results: A total of 49 full texts were included for analysis. There was evidence of the importance of trust, agreement and bond in accordance with Bordin's model. The results also highlighted the importance of greater clarity on supervisory goals, and the tasks to support these goals, to effectively address competing priorities and roles within supervision. Non‐hierarchical relationships were advocated, although supervisors must remain impartial in their assessment and monitoring roles. The influence of the wider practice community and situated learning through legitimate peripheral participation are documented. A model of General practice (GP) supervision is proposed that integrates the findings. Conclusions: GP supervision requires a greater emphasis than is suggested by the working alliance model, both on the clarity of expectations and the appreciation of the multiple roles and competing priorities of both trainee and supervisor. Furthermore, as GP supervision develops within the rising workload of contemporary general practice, the role of the wider community of practice may become more prominent. We have adapted the working alliance model for postgraduate General practice (GP) supervision, emphasising the explicit sharing of expectations relating to goals, tasks and roles to facilitate negotiation and agreement. Abstract : Expanding the notion of a working alliance as a means for enabling effective supervision in postgraduate GP training, the authors report the importance of considering clarity, roles, power and the socio‐cultural context.